Immunoglobulin G Deficiency-Associated Septic Arthritis Identified Following Corticosteroid Injection and Knee Arthroscopy: A Case Report. Issue 3 (July 2016) - Buckley, Patrick S.; Kane, Justin; Ciccotti, Michael G.
Abstract : Case: We present the case of a patient who had worsening pain following intra-articular knee corticosteroid injection and who subsequently underwent arthroscopic partial meniscectomy with positive intraoperative cultures for Staphylococcus lugdunensis . He was treated with multiple irrigation and debridements, and subsequent work-up yielded a diagnosis of immunoglobulin G (IgG) deficiency. We believe that it is critical to maintain a high index of suspicion for underlying immune deficiency when faced with atypical presentations of infections or atypical bacteria in otherwise healthy patients. Conclusion: Knee arthroscopy for the treatment of meniscal tears is one of the most common procedures performed by orthopaedic surgeons in the United States. Patients with an antibody deficiency may have a limited or reduced immune response when presented with a pathogen foreign to the body. This may place the patient at an increased risk of infection and should be addressed through referral to the appropriate subspecialists when recurrent or atypical infection presents to the orthopaedic surgeon.